Students’ Perceptions toward the Use of Short Videos based Social Media in Learning English at Universitas Negeri Padang - Nurul Natasa; Carbiriena Solusia (Journal of English Language Teaching, 2022)
This research purpose to examine students’ perceptions toward the use of short videos based social media in learning English. The writer used an online questionnaire and interview for this research, which included 33 statements for questionnaire and 8 key questions for interview. The participants were 34 students from third year at English Department Universitas Negeri Padang. The findings from the data analysis, most of the students give a positive perception on the use of social media in learning English. The students used social media for learning and improving their English skill. They chose YouTube as the most frequently used application to improve their English skill. Then, they stated that using social media make them happy, challenged and helped when learning English. The students also mentioned that learning English can add new knowledge, develop their skills in speaking and writing and social media can improve their listening skill. Besides, there were several perspective faced by students, they get confused when learning English and do not know who to ask and they feel bothered with advertisement suddenly appeared when their learning English in social media.